An investigation into the effect of knee braces on the lower limb kinematics of badminton players - Earey, L.; Richards, M.; Brouner, J. (World Congress of Performance Analysis of Sport XII, 2018)
Badminton players are prevalent to experiencing lower limb injures with 16.7% occurring in the knee (Fahlstrom et a!.. 1997). the knee joint provides stability when performing technical movements such as a lunge by maintaining stability during frontal and transverse plane movements and decreases the risk of injury to surrounding joints (Thijs et o/., 2007). With 97% of orthopaedic surgeons prescribing braces to their patients (Rishiraj etal.. 2009). there is limited research in terms of the impact of knee braces used in the non-injured population due to concerns of decreased or impaired performance. Purpose: The purpose of this study was to investigate the lower limb kinematics of Badminton players in both a braced condition and a non-braced condition during a lunge. Methods: 8 male Badminton players were recruited to take part in the study (Age: 21.5 ± 0.76 years: Mass: 72.5 ± 6.36 kg; Stature: 178.4 ± 4.44 cm). 3D motion analysis capture was used to analyse the angle of the hip. knee and ankle joint with a primary focus on the knee. Surface electromyography was used to measure muscle activation of the bicep femoris. rectus femoris, medial gastrocnemius and tibialis anterior. The angle measurements and muscle activation levels were collected at the point of initial contact, maximum flexion and the recovery phase. Angular velocity of the hip. knee and ankle were also analysed in two specific time points: initial contact to maximum flexion and maximum flexion into the recovery phase. Results: Significant difference was identified at the hip (130.6° ± 9.3° (NB). 127.4° ± 9.9° (B). P=0.010) and knee (170.2° ± 5.4° (NB). 164.8° ± 3.1° (B). P=0.001) at the contact phase and knee (172.0° ± 10.5° (NB). 170.2° ± 3.9° (B). P=0.004) in the recovery phase. There was no significance identified in the hip. knee or ankle at the point of maximum flexion (P>.05). also no statistical difference was identified in the angular velocities of the hip. knee or ankle joints throughout the lunge (P>.05). There was no significant difference identified in the muscle activations of the rectus femoris, bicep femoris. medial gastrocnemius and tibialis anterior throughout the lunge (P>.05). Conclusion: This study provided evidence that knee bracing had affected the hip and knee joints in the contact phase of the lunge and also thekneejoint in the recovery phase. This differs to the findings of Singer & Lamontage (2007) as their results suggest that the brace has no significant effect on the knee at the point of initial contact (P>.05). Huang etal. (2013) identified that the knee joint having a greater range of motion increases the reach range of the player and therefore improving the possibility of making the shot. Hence it can be stated that the brace restriction observed in the contact and recovery phases at the hip and knee joint can negatively impact performance. However, the brace